Motion of an Articulated Vehicle with Two-Dimensional Sections Subject to Lateral Obstacles - Antonyuk, E. Ya; Zabuga, A. T. (International applied mechanics, 2016)
Some aspects of the geometry, kinematics, and dynamics of a three-section robotic vehicle with a front steerable wheel are studied. The constraints between the wheels and the flat ground are assumed nonholonomic. The vehicle moves in a narrow L-shaped corridor. A path for the characteristic points of the sections of the robot is designed. A dynamic model of the system is developed. The maximum possible dimensions of the robot that allow its unimpeded and non-stop motion are determined. The kinetostatic analysis of the load on a three-section vehicle moving along a planned path is modeled. The holonomic and nonholonomic constraint reactions between the wheels and the ground and in the joints between the sections are determined